Teachers’ attitudes towards inclusive education of children with ASD: A review of Russian and foreign research - R. M. Aysina; A. A. Nesterova; T. F. Suslova; V. V. Khitryuk (Образование и наука)
Introduction. Contemporary psychological and pedagogical studies emphasise that the success of inclusive education of children with autism spectrum disorders (ASD) depends largely on teachers’ readiness and ability to understand students’ with ASD specific needs and take them into account when implementing learning technologies. Thus, it is extremely important to investigate teachers’ attitudes towards educational inclusion of students with autism and identify factors, which may facilitate or hinder teachers’ readiness to work with this category of students in an inclusive format.Aim. On the basis of an analytical review of Russian and foreign academic publications, the aims of the research were the following: to identify and specify the attitudes of teachers to the educational education of children with ASD; to reveal the factors that determine educators’ readiness to teach children with ASD.Methodology and research methods. The theoretical and methodological framework of the research involves social and psychological concepts of an inclusive culture formation in the society. The authors used the methods of theoretical and comparative analysis, systematisation and generalisation of research publications and materials concerning the origins of stereotypical views of different social groups towards children with autism and the problems of professional training of teachers to work in the conditions of inclusion.Results and scientific novelty. The teachers’ attitudes towards children with ASD are highlighted and described on the basis of a complete and complex review of academic publications, which was undertaken for the first time. The authors identify the reasons for positive attitude towards this kind of inclusion and barriers preventing the perception of students with autism as full participants in the educational process. The rejection of idea concerning the possibility and effectiveness of mutual learning of schoolchildren with normative development and with ASD results from the teachers’ characteristics (lack of awareness about the heterogeneity of autism and its manifestations, uncertainty in own forces and abilities to interact with children with expressed emotional and behavioural disorders) and from the lack of methodological and advisory assistance, including the absence of support by an interdisciplinary team of specialists. The age and profile of teachers’ professional activities may also be influenced by the willingness to work in the conditions of inclusion with children with ASD. The recommendations for change in negative attitudes of general education school teachers to the discussed type of inclusion are proposed.Practical significance. The research results can be used to develop a set of measures for improving the inclusive culture of teachers and eliminate their skepticism about teaching in mainstream educational institutions for children with ASD. Moreover, the present findings might help to design specific technologies for interaction with children both in the educational context and in the widest range of social situations.